PELAYANAN PERPUSTAKAAN TERTUTUP PADA MASA COVID-19 DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Irma Hermayanty; Agung Gumilar; Aliman Solahudin; Miftah Al Firdaus; Opik Renaldi; Rio Fajar Maulana (LPPM UNSAP & FISIP UNSAP, 2021)
is study aims to determine, obtain objective data and information about the Closed Service during the Pandemic at the Archives and Libraries Service of Sumedang Regency. The method used in this research is qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this research, there are obstacles regarding closed services during the pandemic at the Sumedang Regency Archives and Library Service, namely: library services, supporting facilities, discipline application, and information technology. Efforts to overcome obstacles include improving services to the community during the pandemic, utilizing facilities and infrastructure, implementing employee work discipline and utilizing information technology in closed services during the pandemic at the Sumedang Regency Archives and Library Service.